Edukasi Kesehatan Reproduksi dan Usia Perkawinan Remaja dalam Upaya Perwujudan Generasi Berkualitas - Dewi, Ika Nurani; Sukri, Akhmad; Firdaus, Laras; Efendi, Ismail; Kurniawan, Ade; Wulandari, Wulandari; Febriani, Puput (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Indonesia is one of the countries with relatively high rates of early marriage compared to others, which indirectly correlates with various issues, including reproductive health. Reproductive health is a crucial aspect of building the quality of future generations. Through community service programs in the form of reproductive health education activities, it is hoped to contribute to enhancing understanding of reproductive health and the age of marriage among adolescents, particularly in the region of Lombok Island, West Nusa Tenggara. The methods used include the stages of: 1) planning; 2) implementation; and 3) reflection. The education activities involve adolescent boys and girls from Parampuan Village, West Lombok Regency. The results of the community service activities show that participants can understand the importance of reproductive health early on and actively participate in educational activities, as evidenced by attendance rates of over 70%. Participants also responded positively to the educational activities. Thus, community service in the form of reproductive health education can: 1) improve adolescents' understanding of reproductive health; 2) raise awareness among adolescents regarding the ideal age of marriage; and 3) ensure effective implementation of educational activities.